2020
DOI: 10.3390/cancers12092393
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Clinicopathological Significance of FADD Upregulation in Head and Neck Squamous Cell Carcinoma: A Systematic Review and Meta-Analysis

Abstract: Fas-associated death domain (FADD) upregulation, i.e., gene amplification, protein phosphorylation and/or overexpression, has shown promising prognostic implications in head and neck squamous cell carcinoma (HNSCC). This systematic review and meta-analysis aims to evaluate the clinicopathological and prognostic significance of FADD upregulation in HNSCC. We searched studies published before February 2020 through PubMed, Embase, Web of Science, Scopus and Google Scholar. We evaluated the quality of the studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 81 publications
1
18
0
Order By: Relevance
“…Free N-terminal FLIP fragment can interact with TRAF1/2 induce NF-κB activation [ 44 ]. Recently, FADD upregulation or S194 phosphorylation are important prognostic biomarkers in multiple cancer progression, especially in OSCC [ 45 47 ]. Moreover, constitutively phosphoryl-mimicking mutation of FADD also enhances Notch-1 signaling in muscle regeneration through promoting ERK phosphorylation is consistent with our finding in oral cancer cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Free N-terminal FLIP fragment can interact with TRAF1/2 induce NF-κB activation [ 44 ]. Recently, FADD upregulation or S194 phosphorylation are important prognostic biomarkers in multiple cancer progression, especially in OSCC [ 45 47 ]. Moreover, constitutively phosphoryl-mimicking mutation of FADD also enhances Notch-1 signaling in muscle regeneration through promoting ERK phosphorylation is consistent with our finding in oral cancer cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, a study found that high FADD expression always results in worse OS, DSS, and DFS in patients with HNSCC and thus has potential values for prognostic prediction and treatment planning development [ 26 , 27 ]. A meta-analysis has found that immunohistochemical assessment of FADD could be incorporated into the prognostic evaluation of HNSCC [ 28 ]. In addition, NKX2-3 is a member of the NKX family, which is a series of the homeodomain transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, BZW1 and CAMK2A were not reported in SCC tumors yet; however, they were identified as prognostic markers in non-SCC tumors [46][47][48][49]. In the past, several prognostic biomarkers or gene sets have been published of which some have been confirmed by systematic reviews and meta-analyses for HNSCC more recently [50][51][52]. It is worth noting that none of them are included in our list of survival-related candidate genes and consequently are not part of the prognostic 18 gene signature for risk prediction.…”
Section: Discussionmentioning
confidence: 99%